2017
DOI: 10.1038/ncomms14988
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced superconductivity accompanying a Lifshitz transition in electron-doped FeSe monolayer

Abstract: The origin of enhanced superconductivity over 50 K in the recently discovered FeSe monolayer films grown on SrTiO3 (STO), as compared to 8 K in bulk FeSe, is intensely debated. As with the ferrochalcogenides AxFe2−ySe2 and potassium-doped FeSe, which also have a relatively high-superconducting critical temperature (Tc), the Fermi surface (FS) of the FeSe/STO monolayer films is free of hole-like FS, suggesting that a Lifshitz transition by which these hole FSs vanish may help increasing Tc. However, the fundame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 30 publications
2
58
0
Order By: Relevance
“…Strong intensity appears at the BZ center as the Se decreases. We will explain below that this originates from an electron band in the unoccupied side, similar to the case of K deposited FeSe/STO monolayer [12] and K deposited bulk FeTe 1-x Se x [23].…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…Strong intensity appears at the BZ center as the Se decreases. We will explain below that this originates from an electron band in the unoccupied side, similar to the case of K deposited FeSe/STO monolayer [12] and K deposited bulk FeTe 1-x Se x [23].…”
mentioning
confidence: 75%
“…The FeSe/STO monolayer films possess a simple FS topology characterized by large electronlike pockets at the M point and the absence of hole-like pockets at Γ [8,9,12], which differs from that of FeSe bulk materials and most of the iron-pnictide superconductors [19]. We show in Fig.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Observations of a superconducting T c as high as 100 K in a monolayer (ML) FeSe/SrTiO 3 (STO) system [1][2][3] have intensified interest in electron-doped FeSe systems [4][5][6]. In the FeSe/STO system, electron transfer from the STO substrate to FeSe appears to be a key ingredient for realizing superconductivity [2,7], and additional electron doping to the system by potassium (K) dosing increases T c [8]. Moreover, surface doping experiments by K dosing [9][10][11][12], Na dosing [13], and liquid gating [14] have shown that electron doping can also increase T c for bulk, thick-film, and multilayer FeSe.…”
mentioning
confidence: 99%